The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0051294
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Repair by the Activation of Cell Survival Signalling Cascades during the Early Stages of Rat Parkinsonism

Abstract: Here we report a previously unknown self repair mechanism during extremely early stages of rat Parkinsonism. Two important cell survival signaling cascades, Phosphatidylinositol-3 kinases (PI3K)/Akt pathway and extracellular signal-regulated kinase/mitogen-activated protein kinase (ERK/MAPK) pathway, could be responsible for this potential endogenous rescue system. In the 6-hydroxydopamine-lesioned rat, the phosphorylated p44/42 MAPK and its downstream target, the phosphorylated Bad at Ser 112, were up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Acute pulmonary injury also affects newborns with intrahepatic cholestasis of pregnancy as well as patients with acute liver failure and cirrhosis . Once injured, self‐repair mechanisms are evoked, prompting the release of various growth factors and cytokines, such as vascular endothelial growth factor‐A and the chemokine fractalkine . These molecules activate survival signals, such as Akt and ERK, in turn leading to endothelial cells (ECs) proliferation and pathological angiogenesis .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute pulmonary injury also affects newborns with intrahepatic cholestasis of pregnancy as well as patients with acute liver failure and cirrhosis . Once injured, self‐repair mechanisms are evoked, prompting the release of various growth factors and cytokines, such as vascular endothelial growth factor‐A and the chemokine fractalkine . These molecules activate survival signals, such as Akt and ERK, in turn leading to endothelial cells (ECs) proliferation and pathological angiogenesis .…”
mentioning
confidence: 99%
“…Once injured, self‐repair mechanisms are evoked, prompting the release of various growth factors and cytokines, such as vascular endothelial growth factor‐A and the chemokine fractalkine . These molecules activate survival signals, such as Akt and ERK, in turn leading to endothelial cells (ECs) proliferation and pathological angiogenesis . These findings raise the possibility that this initial pulmonary injury plays a role in late angiogenesis following CBDL.…”
mentioning
confidence: 99%
“…Under pathological conditions, astrocytes could release neurovascular trophic factors, e.g., glial cell line-derived neurotrophic factor (GDNF), brain-derived neurotrophic factor (BDNF), stromal cellderived factor-1 (SDF-1), and vascular endothelial growth factor (VEGF)-A (Miyazaki et al, 2001;Argaw et al, 2012;Mele and Jurič, 2014;Shin et al, 2014). As has been well demonstrated, SDF-1, BDNF, and GDNF were capable of activating the phosphatidylinositol 3-kinase (PI3K)/AKT and/or extracellular signal-regulated kinase/mitogenactivated protein kinase (ERK/MAPK) signaling pathways in glia, while the reactive PI3K/AKT signal pathway could further improve astrocytes to express VEGF and angiopoietin-1 (Ang1) Lui et al, 2012;Jang et al, 2014). Due to their pivotal role in the nervous system, astrocytes are now recognized as key participants in brain development, function, and disease.…”
Section: Introductionmentioning
confidence: 95%
“…GDNF-epithelial growth factor receptor 1 (EGR1) pathway activation is critical in renal epithelial cell apoptosis and migration in diabetic renal embryopathy (13). In addition, GDNF, nestin and glial fibrillary acidic protein (GFAP)-positive reactive astrocytes appeared at an early stage in 6-hydroxydopamine-induced Parkinsonism in rats, which suggested the existence of endogenous neuroprotective mechanisms that act via the release of BDNF and GDNF from GFAP-positive immunoreactive astrocytes (14). However, one recent study indicated that GDNF treatment did not affect neuronal survival but another neurotrophic factor, neurotrophin 3, was able to enhance the survival of enteric ganglion cells in H 2 O 2 -treated cultures (15).…”
Section: Introductionmentioning
confidence: 99%
“…High intracellular activation of GDNF downstream pathways triggers neuronal differentiation, while low-level activation of GDNF signaling is crucial for the maintenance of the progenitor state (18). In addition, the ERK/MAPK pathway, instead of the phosphoinositide 3-kinase/Akt (PI3K/Akt) pathway, was proposed to be the key endogenous neuroprotective mechanism, acting via the release of bone-derived neurotrophic factor (BDNF) and GDNF from nestin and GFAP-positive reactive astrocytes in the 6-hydroxydopamine-induced rat model of Parkinson's (14). Furthermore, a recent study demonstrated that mechanical and thermal hypersensitivity was correlated with the structural changes and loss of GDNF/ Akt signaling in injured limbs 7 days after chronic constrictive injury was induced.…”
Section: Introductionmentioning
confidence: 99%